The Abandoned Gospel: Confronting Neo-Pentecostalism and the Prosperity Gospel in Sub-Saharan Africa - Barnes, Philip W.; Bhasera, Bazil; Ojo, Matthews A.; Rantho, Jack; Yoakum, S. Trevor; Zulu, Misheck (Maiden Publishing House, 2021)
Nearly one hundred years ago, American theologian J. Gresham Machen declared that “naturalistic liberalism is not Christianity at all.” By this declaration, Machen was saying that Liberalism is not an alternate form of Christianity that one can critique on certain points of doctrine and engage in a debate. Instead, Machen was saying that Liberalism is an altogether different religion. The difference between Christianity and Liberalism was not like the difference between Methodism and Presbyterianism. The difference was like the difference between Islam and Hinduism—two completely different religions with completely different presuppositions and approaches to the search for Truth.The authors of this book contend that the evangelical church in Africa (and indeed around the world) must rise up and say the same thing about any and all aberrant faiths and false churches. This particular volume will lay this charge against the various movements and groups that can be categorized under the heading of the Prosperity “Gospel” and Neo-Pentecostalism. These two (overlapping) groups represent a religion that has abandoned the gospel and is now preaching a gospel that is no gospel at all. This message has been stripped of its power to save, its power to transform, and its power to reconcile. Only by returning to the gospel can the church in Africa be a useful tool in her Master’s hands. May God grant us the grace to “contend for the faith that was delivered to the saints once for all.”